2008
DOI: 10.1007/s00134-008-1048-1
|View full text |Cite
|
Sign up to set email alerts
|

Gene profiling in human blood leucocytes during recovery from septic shock

Abstract: These results are the first description of variations in expression of key inflammatory genes in the course of the septic shock recovery period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
55
0
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 26 publications
3
55
0
6
Order By: Relevance
“…[25] Levels were also increased in septic patients and inversely correlated with survival. [26] Serum levels of S100A8/S100A9 were found to correlate better with disease activity and joint destruction in various inflammatory arthritides than classical markers of inflammation. [27] Much research has been done to assess the levels of inflammatory marker CRP, ESR, IL-6 etc in chronic periodontitis.…”
Section: Alarmins As Biomarkers Of Diagnosis and Prognosismentioning
confidence: 95%
“…[25] Levels were also increased in septic patients and inversely correlated with survival. [26] Serum levels of S100A8/S100A9 were found to correlate better with disease activity and joint destruction in various inflammatory arthritides than classical markers of inflammation. [27] Much research has been done to assess the levels of inflammatory marker CRP, ESR, IL-6 etc in chronic periodontitis.…”
Section: Alarmins As Biomarkers Of Diagnosis and Prognosismentioning
confidence: 95%
“…Payen et al reported that, in patients with septic shock, mRNA S100A12 expression by circulating leukocytes was decreased during the recovery phase [46]. One possible function of S100A12 in host defense during infection and sepsis is its role as a DAMP.…”
Section: Rage During Abdominal Sepsismentioning
confidence: 99%
“…Payen et al [68] assessed blood leucocytes gene profiling in the course of the septic shock recovery period and tested the relation between encoding gene expression and protein level in 17 septic shock patients. Gene expression levels were studied on a dedicated microarray of 340 genes involved in inflammatory processes.…”
Section: Miscellaneamentioning
confidence: 99%